2013
DOI: 10.3390/md11124741
|View full text |Cite
|
Sign up to set email alerts
|

New Sinularianin Sesquiterpenes from Soft Coral Sinularia sp.

Abstract: Four new sesquiterpenes, sinularianins C–F (3–6), together with known sinularianins A (1) and B (2) were identified from a South China Sea soft coral Sinularia sp. Compounds 1–6 were evaluated for inhibition of NF-κB activation using the cell-based HEK293 NF-κB luciferase reporter gene assay. Compounds 1 and 4 were exhibited a potent effect with inhibitory rates of 41.3% and 43.0% at the concentration of 10 µg/mL, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…(Dongluo Is., Hainan Province, China). 764 Perezoperezone 840 and curcuperezone 841 (Pseudopterogorgia rigida, Caribbean Sea) are envisaged to arise, in the case of 840, from non-symmetrical dimerisation of known cometabolite perezone 765 and in the case of 841, through coupling of perezone and a-curcumene. 766 Flexibilisquinone 842 (cultured specimen of Sinularia exibilis) 767 was claimed to be the enantiomer of sarcophytonone (Sarcophyton crassocaule) 768 based upon optical rotation data (842 [a] D À19.6, sarcophytonone [a] D +5.8).…”
Section: Cnidariansmentioning
confidence: 99%
“…(Dongluo Is., Hainan Province, China). 764 Perezoperezone 840 and curcuperezone 841 (Pseudopterogorgia rigida, Caribbean Sea) are envisaged to arise, in the case of 840, from non-symmetrical dimerisation of known cometabolite perezone 765 and in the case of 841, through coupling of perezone and a-curcumene. 766 Flexibilisquinone 842 (cultured specimen of Sinularia exibilis) 767 was claimed to be the enantiomer of sarcophytonone (Sarcophyton crassocaule) 768 based upon optical rotation data (842 [a] D À19.6, sarcophytonone [a] D +5.8).…”
Section: Cnidariansmentioning
confidence: 99%
“…Representative examples of spirocyclic butenolides isolated from the soft coral Sinularia sp . are shown in the Scheme , top . Therefore, much attention has been given to the development of synthetic methods allowing for their preparation, in particular in a stereocontrolled manner .…”
Section: Methodsmentioning
confidence: 99%
“…are shown in the Scheme 1, top. [2] Therefore, much attentionh as been given to the development of synthetic methods allowing for their preparation, in particulari nas tereocontrolled manner. [3][4][5][6] The most commona pproachr elies on the application of dienolates A for their preparation.I th as been demonstrated that silyloxy furans serve as their synthetic equivalents readily participating in the vinylogous Mukayama-aldol or Mukayama-Michael and related reactions proceeding in ar egioselective fashion in the 5-position of the furan ring.…”
mentioning
confidence: 99%
“…These corals occur abundantly in the Indo-Pacific where they are one of the most dominant species of large ecological importance (Benayahu and Loya, 1977). Moreover, the members of this genus are pharmaceutically important because they produce a wide range of bioactive metabolites (Aceret et al, 1998;Ahmed et al, 2006;Chen et al, 2015;Lakshmi and Kumar, 2009;Yang et al, 2013) that exhibit several different biological activities (Aceret et al, 1998;Li et al, 2005;Su et al, 2008). However, the ecological dominance of the Sinularia species is challenged by coral-bleaching events, where up to a 90% mortality rate has been recorded (Fabricius, 1995;Loya et al, 2001).…”
Section: Introductionmentioning
confidence: 97%